El Pantanal: un ejemplo del impacto geomorfológico sobre el ambiente - Tricart, Jean (Investigaciones Geográficas: Una mirada desde el sur, 1982)
The Pantanal trough is located at the border line of the "couverture tabulaire" at Mato Grosso Plateau, under control of faults and Precambrian metamorphic and crystalline continental crust with Apalachian Eocambrian sedimentary landforms. Modern alluvial formations have been formed at least 200 m below present sea level, having around 300 m thickness. Thus, the Pantanal is a tectonic trough, completely bordered by the 200 m contour line. Subsidence explains gentle slopes, which are lesser than 1%. At the sheet flood fan axe. River floods are running slowly from neighbor mountains areas, allowing a grassland support for more than 5.000.000 of cattle. Pantanal alluvial deposits have built enormous coalescent sheet flood fans. The largest one is Taquari, which cross over residual mountain chains at the right hand border of the Paraguay, covering "glacis" (bahadas) lying at its ground. On the contact between this sheet flood fans and the "glacis" there is a series of receptacle lakes, which are by the Paraguay floods. Some lakes restore water to the Paraguay River during its low level after floods. During recent Quatemary dry periods the high Paraguay basin was endorreic. So, a number of Pantanal sheet flood fans are digged by wind erosion, forming troughs. These troughs are partly covered by lagoons and partly by amphibious vegetation, thus increasing runoff deficit. Therefore, the Pantanal plays an important role on the Paraguay hidrology, emphasizing floods but increasing runoff deficit. It has been suggested to build large dams to regulate water flow in the rivers, near their entrances into the Pantanal. However, this radical change in environmental management needs a lot of knowledge, specially on this very complex and feeble environment, where, as a consequence, investments are very expensive.